Mathematics Critical Thinking Skills for The Third Grade Elementary School Students on Fractions Material - Fitriani, Fildzah; Kowiyah (MIMBAR PGSD Undiksha, 2022)
In learning mathematics, critical thinking is needed to solve problems in various ways including interpreting, analyzing and evaluating. This study aims to analyze the critical thinking of third grade elementary school students in solving problems on the subject of fractions. The research was conducted at Elementary school by involving 26 students as the subject. This research used qualitative method. The data collection techniques used description tests and interviews. The description tests were reviewed based on four critical thinking indicators, namely interpreting, analyzing, evaluating and inference. This qualitative data processing technique is reducing data, presenting data, and drawing conclusions. The validity of the data was carried out using a triangulation technique, namely the results of student description tests, and interviews were triangulated to obtain a description of students' critical thinking skills in solving math problems with fractions. The results showed that students with high critical thinking met the four indicators, students who had moderate critical thinking only met two indicators, and students who had low critical thinking did not meet the four indicators. In conclusion, students' critical thinking skills were low. They could not understand the problem well and had not solved it properly. Meanwhile, students who think highly critically are able to understand questions about fractions, to analyze, to choose the right method, and to conclude clearly and logically.